2012
DOI: 10.1039/c2ra20769a
|View full text |Cite
|
Sign up to set email alerts
|

An amorphous wrapped nanorod LiV3O8 electrode with enhanced performance for lithium ion batteries

Abstract: To achieve a good combination of high capacity, cyclability and rate capability in an electrode is still a great challenge for lithium-ion batteries, especially those used for electric vehicles. The present work has developed a simple and effective strategy to solve this problem in the layer structured LiV 3 O 8 positive electrode. This has the highest theoretical capacity of the currently available positive electrodes but it has not yet been achieved in practice along with high rate capability. In our approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The outstanding high rate capability of NR‐500 cathode is apparently attributed to the nanorod structure, in which Li ions can rapidly reach the active sites along the radial direction. Moreover, it has been demonstrated that the growth orientation and state of the particle surface play important roles in the diffusion of Li ions and the rate capability, Based on the above discussion, we speculated that the [100] growth orientation of the nanorods may be beneficial to the Li ion diffusion in the LiV 3 O 8 , this viewpoint was previously proposed by Zhu and co‐workers . However, the dynamic and thermodynamic characteristics of lithium ion diffusion in the LiV 3 O 8 crystals are still unclear, thus the favorable growth orientation of LiV 3 O 8 nanorods for lithium transport needs further research.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The outstanding high rate capability of NR‐500 cathode is apparently attributed to the nanorod structure, in which Li ions can rapidly reach the active sites along the radial direction. Moreover, it has been demonstrated that the growth orientation and state of the particle surface play important roles in the diffusion of Li ions and the rate capability, Based on the above discussion, we speculated that the [100] growth orientation of the nanorods may be beneficial to the Li ion diffusion in the LiV 3 O 8 , this viewpoint was previously proposed by Zhu and co‐workers . However, the dynamic and thermodynamic characteristics of lithium ion diffusion in the LiV 3 O 8 crystals are still unclear, thus the favorable growth orientation of LiV 3 O 8 nanorods for lithium transport needs further research.…”
Section: Resultsmentioning
confidence: 76%
“…Based on the theoretical calculation, monoclinic LiV 3 O 8 can accommodate the intercalation/deintercalation of around three Li + ions, and release a capacity of over 280 mAh g −1 . Specifically, the amorphous wrapped LiV 3 O 8 nanorod could deliver a very high lithium storage capacity of 388 mAh g −1 , corresponding to a more than four‐electron transfer reaction . Despite its high specific capacity, LiV 3 O 8 still suffers from poor rate capability and unexpected capacity fade.…”
Section: Introductionmentioning
confidence: 99%
“…The high capacity was attributed to the unique structuring, where the amorphous LiV3O8 wrapping provided a 3D pathway for Li + diffusion to the favourable (100) plane, while further, the amorphous wrapping may itself provide Li + storage before transfer to the (100) plane. Also encouraging, was the high rate performance of the wrapped LiV3O8 nanorods, where large capacities of 102 mA h g -1 could be obtained at a rate of 40 C (a ~45 s discharge), and up to ~80 mA h g -1 at a rate of 50 C [368]. Both the stable, high capacity cycling and high rate performance of this example outline the tremendous potential of the LiV3O8 cathode.…”
Section: 14mentioning
confidence: 67%
“…In another recent example, Shi and co-workers [368], demonstrated significantly high capacity in their [100]-oriented LiV3O8 nanorods, which were encased in an amorphous LiV3O8 wrapping (Fig. 31).…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation